Leveling the Peaks and Troughs of the Demographic Cycle: An Application to School Enrollment Rates: A Reply - Wachter, Michael L.; Wascher, William L. (The Review of Economics and Statistics, 1991)
Michael L. Wachter, William L. Wascher, Leveling the Peaks and Troughs of the Demographic Cycle: An Application to School Enrollment Rates: A Reply, The Review of Economics and Statistics, Vol. 73, No. 3 (Aug., 1991), pp. 575-576